2020
DOI: 10.1002/celc.202001190
|View full text |Cite
|
Sign up to set email alerts
|

Vacancy‐Induced Oxygen Reduction Activity in Janus Transition Metal Dichalcogenides

Abstract: In the past few years, transition metal dichalcogenides (TMDs) have attracted extensive attention in the development of oxygen reduction reaction (ORR) catalysts. Herein, a new family of TMDs, Janus TMDs, as ORR catalyst has been investigated by employing the density functional methods. Our results indicated that the pristine Janus TMDs (MoXY, X, Y=S, Se, Te; X≠Y) and MoXY with X vacancy have poor ORR activity. In contrast, MoXY with Mo vacancy, i. e., MoXY‐SV‐Mo are good ORR catalysts due to the moderate adso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 53 publications
(55 reference statements)
1
2
0
Order By: Relevance
“…Due to the difference in subversion between atoms, Mo and chalcogenide elements form three kinds of sulfides MoSeS, MoSTe, and MoSeTe with different lattice constants. After structural optimization, the lattice constants of isolated monolayer MoSeS, MoSTe, and MoSeTe are a = b = 3.215 Å, 3.323 Å, and 3.391 Å, respectively, which is consistent with previous works [50,51]. The structure of MoSeS as a prototype is given in figure 1(b).…”
Section: Structural Optimizationsupporting
confidence: 85%
“…Due to the difference in subversion between atoms, Mo and chalcogenide elements form three kinds of sulfides MoSeS, MoSTe, and MoSeTe with different lattice constants. After structural optimization, the lattice constants of isolated monolayer MoSeS, MoSTe, and MoSeTe are a = b = 3.215 Å, 3.323 Å, and 3.391 Å, respectively, which is consistent with previous works [50,51]. The structure of MoSeS as a prototype is given in figure 1(b).…”
Section: Structural Optimizationsupporting
confidence: 85%
“…It has been reported that the excellent catalytic activity of TMDs can be mainly attributed to the vacancies, edge sites, doping, impurities, and grain boundaries. [29,114,115] Er et al [50] found that the recently synthesized family of Janus TMDs can be promising candidates for the HER due to the inherent structural asymmetry. They specifically identified Janus WSSe monolayer as a promising candidate since its basal plane can be activated without large applied tensile strains and in the absence of a significant density of vacancies.…”
Section: Hydrogen Evolution Reaction (Her)mentioning
confidence: 99%
“…The presence of a chalcogen vacancy can effectively decrease the interfacial distance between the metal and transition metal dichalcogenide (TMD), thereby reducing both the tunnel barrier and contact resistance [20]. Mo vacancy in MoXY (Y = S, Se, Te; X not equal Y) can effectively modulate the ORR activity of Janus TMDs [21]. Lastly, a dopant-induced modification can influence the optical and magnetic properties of TMDs [22].…”
Section: Introductionmentioning
confidence: 99%